Optics of Biological Particles - Hoekstra, Alfons; Maltsev, Valeri; Videen, Gorden (NATO Science Series II: Mathematics, Physics and Chemistry, Mathematics, Physics and Chemistry, 2007)
The NATO Advanced Research Workshop on "Optics of Biological Particles" met in Novosibirsk, Russia 3 - 6 October, 2005. The focus of the meeting was the potential of light scattering in the detection and characterization of biological particles, on novel detection systems using polarized light scattering, imaging (microscopy), inelastic scattering, absorption, and emission over all EM spectral regions. The concept for the ARW came about at the culmination of a NATO Science for Peace Project, headed by Alfons and Valeri. It was thought this would be a convenient vehicle to advertise and demonstrate the apparatus resulting from this multi-year collaboration. Potential applications of the device for bio-aerosol Valeri Maltsev and Alfons Hoekstra. characterization interested the third member of the triumvirate. While the co-chairs were occupied by bureaucratic necessities, the logistics were worked out by the Local Organizing Committee, the seemingly endless number of students and colleagues of Valeri, and especially the fixer Dina Goloshchapova who dealt with all the difficult problems. Optics of biological Gorden Videen, Alfons Hoekstra and Valeri Maltsev at particles encompasses a conference dinner. vii viii Preface great many fields, and our workshop and this volume can only scratch the surface. We were lucky to have a group of outstanding lecturers willing to invest the time to provide illuminating and entertaining lectures on the fundamental research in their fields. This book is a compilation of Valeri Maltsev demonstrates prototype of the Scanning significant contributions Flow Cytometer.